Synthesis and Evaluation of Antiinflammatory and Analgesic Activities of a Novel Series of Substituted-N-(4-methyl-2-oxo-2H-chromen-7-yl) benzamides - Ronad, Pradeepkumar M; Hunashal, Rajesh D; Darbhamalla, Satyanarayana; Maddi, Veeresh S (Arzneimittelforschung, 2008)
A novel series of coumarinyl amides (IVa-1) have been synthesized by reacting 7-amino-4-methylcoumarin (III) with various substituted aromatic acid chlorides. IR, 1H NMR, 13C NMR and HRMS spectral data characterized the structure of the synthesized compounds. The title compounds were screened for in vivo acute anti-inflammatory activity using the carrageenan-induced rat paw edema assay model. Among the compounds tested, 2-chloro-N-(4-methyl-2-oxo-2H-chromen-7-yl)benzamide (IVb) and 4-chloro-N-(4-methyl-2-oxo-2H-chromen-7-yl)benzamide (IVc) showed 60.5 and 62.3% edema protection, respectively, as compared to the standard drug diclofenac (CAS 15307–86–5) (63.5%) after third hour. Compounds N-(4-meth-yl-2-oxo-2H-chromen-7-yl)-4-nitrobenz-amide (IVf) and N-(4-methyl-2-oxo-2H-chromen-7-yl)cinnamamide (IVg) showed moderate activity. The new compounds have been also tested for in vivo analgesic activity. Quantitative structure-activity relationship studies indicated that the chloro substitution at the aromatic ring enhanced the anti-inflammatory activity (IVb and IVc). These compounds were also found to provide significant protection in acetic acid induced writhing animal model, showing remarkable analgesic activity. Compounds IVb and IVc showed 55.1% and 56.3% protection, respectively, as compared to acetylsalicylic acid (CAS 50–78–2) (57.7%).
Keywords: Anti-inflammatories, non-steroidal; Coumarinyl amides, analgesic activity, anti-inflammatory activity, synthesis